Model Pembelajaran dalam Upaya Meningkatkan Kemampuan Berpikir Kritis Matematis Siswa: Model Pembelajaran dalam Upaya Meningkatkan Kemampuan Berpikir Kritis Matematis Siswa - Nurfithriyah, Aisyah Rizki (Jurnal Riset Pendidikan Matematika Jakarta, 2020)
Students’ mathematical critical thinking skills are still low. Therefore, it takes effort to overcome, one of them is using other learning models. This study aims to determine learning models that can improve students' mathematical critical thinking skills. This study is quantitative research using library research methods (literature review). The data used are secondary data from 10 different articles of national and international mathematics education journals, the analysis technique is content analysis. The result obtains 8 learning models that can improve middle level students' mathematical critical thinking skills. These learning models are Realistic Mathematics Education (RME), Creative Problem Solving, Means-Ends Analysis, Problem Based Learning, Brain Based Learning, Contextual Teaching and Learning, Discovery Learning, and Open-Ended Learning. This research is expected to help teachers to consider learning models that can be applied in the class.